COMPETITIVE ADVANTAGES OF POLISH FOOD PRODUCERS ON THE EUROPEN UNION MARKET IN THE POST-ACCESSION PERIOD - Mirosława Braja; Janina Sawicka (Acta Scientiarum Polonorum. Oeconomia, 2017)
Processes and phenomenons that appear within world economy result in the increase of competition on lots of markets, including the food markets. This competition is won by the entities, sectors and countries that possess the advantages which create their competitiveness. Different types of food producers’ competitive advantages may be identified. Mostly pointed out are price advantages and quality advantages. The aim of this paper is to identify the sources of competitive advantages of Polish food producers on the European Union market that appeared within the period 2004–2016. The analysis covered 26 groups of products which were selected according to their significance for Polish agri-food export. The long-term observation let the Authors identify the dominating strategies of competing which were implemented by Polish food producers on the European Union market. Analysis was conducted with the Aiginger’s price-quality approach and was based on the data available within Eurostat Comext database.